2000
DOI: 10.1074/jbc.m908066199
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal Region, C-terminal Region, Nuclear Export Signal, and Deacetylation Activity of Histone Deacetylase-3 Are Essential for the Viability of the DT40 Chicken B Cell Line

Abstract: Histone deacetylases (HDACs) are involved in the deacetylation of core histones, which is related to transcription regulation in eukaryotes through alterations in the chromatin structure. We cloned cDNA and genomic DNA encoding a chicken HDAC, chHDAC-3, which was localized in both the nuclei and cytoplasm in DT40 cells. Although one of the two chHDAC-3 alleles could be disrupted with high efficiency, no homozygous mutants were obtained after a second round of the genetargeting technique due to its necessity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 50 publications
8
77
0
Order By: Relevance
“…Perhaps this could be a reflection of the different cell types used by different laboratories. A sequence present at position 29 -41 of HDAC3 (LALTHSLVL-HYGL) that resembles the canonical NES (⌿n⌿XX⌿X⌿, where ⌿ indicates hydrophobic residues and X indicates any amino acid) has been assumed to function as the NES for HDAC3 (31). Our deletion analysis, however, indicates that the NES resides within residues 180 -313 of HDAC3 and that this sequence is necessary and sufficient for binding to CRM1.…”
Section: Structure-function Analysis Of Hdac3mentioning
confidence: 56%
See 2 more Smart Citations
“…Perhaps this could be a reflection of the different cell types used by different laboratories. A sequence present at position 29 -41 of HDAC3 (LALTHSLVL-HYGL) that resembles the canonical NES (⌿n⌿XX⌿X⌿, where ⌿ indicates hydrophobic residues and X indicates any amino acid) has been assumed to function as the NES for HDAC3 (31). Our deletion analysis, however, indicates that the NES resides within residues 180 -313 of HDAC3 and that this sequence is necessary and sufficient for binding to CRM1.…”
Section: Structure-function Analysis Of Hdac3mentioning
confidence: 56%
“…2A), immunofluorescence studies using anti-HDAC3 antiserum revealed that HDAC3 is located in both the nucleus and cytoplasm of DT40 cells (31). A similar subcellular distribution was observed using an antibody against the FLAG epitope in COS cells transfected with an expression plasmid encoding FLAG-tagged HDAC3 (46).…”
Section: The Unique Extreme C Terminus Of Hdac3 Is Required Formentioning
confidence: 65%
See 1 more Smart Citation
“…This observation led to the hypothesis that HDAC3 may have some unique properties and may not be completely redundant with the other HDACs (Yang et al, 1997). This is also suggested by the differential localization of HDAC3, which, unlike the predominantly nuclear HDACs 1 and 2, can be found in the nucleus, the cytoplasm and at the plasma membrane (Takami and Nakayama, 2000;Longworth and Laimins, 2006). Detailed domain analysis has revealed that the protein contains both nuclear import and export signals, which account for this distinct localization pattern (Yang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, HDAC3 can be found in the nucleus and in the cytoplasm, whereas all other Class I HDAC are strictly nuclear proteins. 25,26 Additionally, unlike HDAC1 and HDAC2, the disruption of HDAC3 gene, which is homologous to yeast protein RPD3, 27 makes DT40 chicken cells non-viable, 25 suggesting specific and non-redundant function of this gene product. Another interesting feature of the human HDAC3 was reported recently by Zhang et al,28 who demonstrated that HDAC3 is necessary and sufficient for silencing the growth-differentiation factor 11 (Gdf11) gene, a TGF-b family member that inhibits cell proliferation.…”
Section: Discussionmentioning
confidence: 99%